The Management of the Productive Socialist Firm - عامر , عبد القادر (Dirasat in Economics and Business, 1980)
This paper aims at studying how the socialist firm is managed and how the producers participate in its management through the principle of "Partners not Wage Workers" and through the Popular Committees, "Committees everywhere' Also the paper shows how the producers participate in planning and in decisionmaking. The productive firm is an open system and takes energy from the environment (human and material resources). It transforms these resources to output which goes back into the environment. This firm operates to satisfy the needs of the people and it does not seek to gain any profit. The paper shows that there is a relationship between ownership and management. Management is controlled by those who own wealth. They either manage by themselves or they choose someone who takes care of management on their behalf. Two sources of authority have been discussed. The formal authority theory and the acceptance theory. These are employed in the capitalist system, where the person who owns IS the one who takes decisions. But it is predicted that the struggle to gain authority will continue between the capitalists and the producers.